GROEL/ES Buffers Entropic Traps in Folding Pathway during Evolution of a Model Substrate. Issue 20 (18th September 2020) - Sadat, Anwar; Tiwari, Satyam; Verma, Kanika; Ray, Arjun; Ali, Mudassar; Upadhyay, Vaibhav; Singh, Anupam; Chaphalkar, Aseem; Ghosh, Asmita; Chakraborty, Rahul; Chakraborty, Kausik; Mapa, Koyeli
Abstract: The folding landscape of proteins can change during evolution with the accumulation of mutations that may introduce entropic or enthalpic barriers in the protein folding pathway, making it a possible substrate of molecular chaperones in vivo . Can the nature of such physical barriers of folding dictate the feasibility of chaperone-assistance? To address this, we have simulated the evolutionary step to chaperone-dependence keeping GroEL/ES as the target chaperone and GFP as a model protein in an unbiased screen. We find that the mutation conferring GroEL/ES dependence in vivo and in vitro encode an entropic trap in the folding pathway rescued by the chaperonin. Additionally, GroEL/ES can edit the formation of non-native contacts similar to DnaK/J/E machinery. However, this capability is not utilized by the substrates in vivo . As a consequence, GroEL/ES caters to buffer mutations that predominantly cause entropic traps, despite possessing the capacity to edit both enthalpic and entropic traps in the folding pathway of the substrate protein. Graphical abstract: Unlabelled Image Highlights: Made an expression-controlled GFP library to study chaperone-dependence in vivo . Simulated a single step of molecular evolution toward GroEL/ES dependence in vivo . GroEL/ES can prevent non-native contacts and take protein out of entropic traps. The model substrate in vivo use GroEL/ES' capacity to remove entropic traps.